Examining the Mediating Effect of Technology Trust on Customer Loyalty in a Regional Banking App - Ayu Kusumaning Rukmi; Raditha Dwi Vata Hapsari; Taufiq Ismail (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The swift expansion of digital banking has amplified rivalry among financial institutions, rendering customer loyalty essential for maintaining long-term success. Grasping the factors that affect users’ ongoing utilization of mobile banking apps is crucial, especially in regional banks like Bank Jatim. This research seeks to analyze how perceived ease of use, perceived usefulness, and perceived risk influence customer loyalty to the JConnect Mobile application, incorporating trust in technology as a mediating factor and gender as a control variable. Based on the Technology Acceptance Model (TAM), the study uses a quantitative explanatory method. Data were gathered from 180 active JConnect Mobile users throughout East Java and examined using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that perceived ease of use, perceived usefulness, and perceived risk greatly affect customer loyalty both directly and indirectly via trust in technology. Additionally, trust in technology acts as a vital intermediary in enhancing the connection between users’ views on technology and their loyalty. On the other hand, gender does not have a notable impact on customer loyalty. To summarize, the results indicate that improving user trust and refining technological features are more critical in promoting loyalty compared to demographic traits, presenting significant managerial insights for digital banking advancement.